2001
DOI: 10.2460/javma.2001.218.873
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary students and psychologic services

Abstract: T here is a paucity of research pertaining to the psychologic components of veterinary medical education; most knowledge is drawn from human medicine. Research in human medicine has illuminated the needs medical students have for psychologic counseling and the barriers these students face in accessing these services. Veterinary students' needs for psychologic services, although assumed to be similar, have not been specifically addressed.Results of research pertaining to human medicine indicate that anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Furthermore, the majority of both staff (88 per cent) and student (79 per cent) respondents rated the necessity of on‐site counselling as ‘very important’ or ‘important’ when all student teaching is based at the veterinary campus. The convenient location of on‐site counselling has previously been reported to increase the access of counselling services by students at American veterinary schools (Kogan and McConnell 2001). Additionally, these students reported that on‐site counselling provided reassurance that their counsellor understood the unique pressures and issues pertinent to veterinary students (Kogan and McConnell 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of both staff (88 per cent) and student (79 per cent) respondents rated the necessity of on‐site counselling as ‘very important’ or ‘important’ when all student teaching is based at the veterinary campus. The convenient location of on‐site counselling has previously been reported to increase the access of counselling services by students at American veterinary schools (Kogan and McConnell 2001). Additionally, these students reported that on‐site counselling provided reassurance that their counsellor understood the unique pressures and issues pertinent to veterinary students (Kogan and McConnell 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Four of the six responding veterinary schools provided some form of additional school-based counselling support, although only two used licensed practitioners which would be conventionally viewed as counsellors. By comparison, a survey of American veterinary schools in 2001 reported that 48 per cent provided on-site counsellors, 27 per cent of whom were fulltime and 73 per cent of whom were part-time (Kogan and McConnell 2001). Counsellors were available for three hours per week at the two UK schools, compared with a mean of 8.6 ± 6.4 hours by part-time counsellors at American schools (Kogan and McConnell 2001), although the number of students supported is not reported.…”
mentioning
confidence: 97%
“…By comparison, a survey of American veterinary schools in 2001 reported that 48 per cent provided on-site counsellors, 27 per cent of whom were fulltime and 73 per cent of whom were part-time (Kogan and McConnell 2001). Counsellors were available for three hours per week at the two UK schools, compared with a mean of 8.6 ± 6.4 hours by part-time counsellors at American schools (Kogan and McConnell 2001), although the number of students supported is not reported. Use of on-site counselling is considered important by veterinary staff and students, particularly when all teaching is based away from central university services (Pickles and others 2012).…”
mentioning
confidence: 97%
See 2 more Smart Citations